Preparation of unidirectional porous AlN ceramics via the combination of freeze casting and combustion synthesis. (20th February 2022) - Wei, Zhilei; Zhang, Zhejian; Zhang, Xiaoyu; Li, Zhiyuan; Li, Tao; Hu, Jiabin; Xu, Shunjian; Shi, Zhongqi
Highlights: Unidirectional porous AlN ceramics (UP-AlNs) were successfully fabricated. The combination of freeze casting and combustion synthesis is economical. The diluent content and solid loading affected the microstructure and open porosity. The UP-AlNs exhibited anisotropic thermal conductivity and compressive strength. The UP-AlNs have promising application prospects as catalyst supporters or filters. Abstract: Unidirectional porous AlN ceramics (UP-AlNs) have attracted great attention for their wide applications in catalyst supports, filters and composite reinforcements. However, traditional fabrication processes usually require high temperature and long production cycle. Herein, UP-AlNs were successfully fabricated via the combination of tertiary butyl alcohol (TBA)-based freeze casting and combustion synthesis route using Al and AlN powders as raw materials. The microstructure, open porosity, thermal conductivity and compressive strength of UP-AlNs can be manipulated by synergistically regulating the AlN diluent content and Al/AlN solid loading of the freezing slurries. The optimal UP-AlNs exhibited controllable structure wavelength ( λ ) and open porosity in a wide range of 21.1-47.1 μm and 54.2%-86.0%, respectively. In addition, the corresponding products also possessed anisotropic thermal conductivity and compressive strength. This novel route for the fabrication of UP-AlNs has the advantages of low cost, energy-saving and high efficiency, which shows significant promise for industrial applications. Graphical abstract: Image, graphical abstract